2021
DOI: 10.21603/2308-4057-2021-2-317-323
|View full text |Cite
|
Sign up to set email alerts
|

Farmed Turkish salmon: Toxic metals and health threat

Abstract: Introduction. Toxic metals in fish, even at low levels, have negative consequences for human health. Even essential metals pose a health threat if consumed in certain quantities. Mercury, cadmium, and lead are the most frequent metals containing in fish. The research objective was to inspect the quality of aquaculture fish found in most major grocery chains across Turkey. Study objects and methods. The present research featured the quantities of Zn, Fe, Cu, Al, Pb, Hg, and Cd in Turkish salmon. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Consumption of groups A and B was more effective in terms of heart health compared to group N due to the high K content. Bat et al (2021) reported the Fe content of large rainbow trout farmed in the Black Sea (similar to groups A and B in the present study) to be 4.80 mg/kg. This literature is very close to the A and B groups in the present study.…”
Section: Vitamins Minerals and Heavy Metals Content Of The Groupssupporting
confidence: 86%
“…Consumption of groups A and B was more effective in terms of heart health compared to group N due to the high K content. Bat et al (2021) reported the Fe content of large rainbow trout farmed in the Black Sea (similar to groups A and B in the present study) to be 4.80 mg/kg. This literature is very close to the A and B groups in the present study.…”
Section: Vitamins Minerals and Heavy Metals Content Of The Groupssupporting
confidence: 86%
“…If the HI is less than 1.0, it is doubtful that there will be evident negative consequences, whereas an HI more than 1.0 suggests the likelihood of negative consequences. When the HI exceeds ten (10), the risk is considered high, persistent, or even severe [1,24,25].…”
Section: Consumer's Health Risk Assessmentmentioning
confidence: 99%
“…10 .The Sentinel-2 satellite used for the study area is a multi-band satellite developed by the European Space Agency (ESA) under the Copernicus Land Monitoring Services. The satellite has 13 spectral bands and spatial resolutions of 10 m, 20 m, and 60 m. 11.…”
mentioning
confidence: 99%